1983
DOI: 10.1002/app.1983.070280213
|View full text |Cite
|
Sign up to set email alerts
|

Deformation band studies of axially compressed poly(p‐phenylene terephthalamide) fiber

Abstract: SynopsisDeformation mechanism of poly(p-phenylene terephthalamide) (PPTA) fiber during axial compression was studied. PPTA fibers were embedded in resin and axialy compressed in a tensile machine. PPTA fibers were then taken out from resin at various stages of compression. Kink band formation was examined by means of polarizing microscopy, X-ray diffraction (WAXD), electron diffraction (ED), and electron microscopy. WAXD pattern of seriously compressed PPTA fiber shows that (200) reflection spots and arcs appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 14 publications
3
21
0
Order By: Relevance
“…In the case of bending, yielding occurs at a relatively low strain of about 0.75% (Greenwood and Rose, 1974). Axial compression and severe bending may induce plastic deformation: Dobb et al (1981) and Takahashi et al (1983) showed the formation of kink bands at 55-60° to the fibre axis when the compressive strain reached about 0.5% (Greenwood and Rose, 1974), consistent with compressive yield stress. Figure 12.20 presents two micrographs, obtained with cross-polarized optical and scanning electron microscopes, of localized bands in the compressed region of a bent fibre.…”
Section: Compression Bending and Torsionsupporting
confidence: 52%
“…In the case of bending, yielding occurs at a relatively low strain of about 0.75% (Greenwood and Rose, 1974). Axial compression and severe bending may induce plastic deformation: Dobb et al (1981) and Takahashi et al (1983) showed the formation of kink bands at 55-60° to the fibre axis when the compressive strain reached about 0.5% (Greenwood and Rose, 1974), consistent with compressive yield stress. Figure 12.20 presents two micrographs, obtained with cross-polarized optical and scanning electron microscopes, of localized bands in the compressed region of a bent fibre.…”
Section: Compression Bending and Torsionsupporting
confidence: 52%
“…An example of kink banding in axially compressed Kevlar* fibers is shown in Figure 1. These compressive kink bands have been observed for well-oriented polymers based on both rigid rod [1][2][3][4][5][6] and flexible [7][8][9][10][11][12][13][14][15] chains. Most of these polymers exhibit nearly linear elastic behavior in compression until the onset of kink banding.…”
Section: Introductionmentioning
confidence: 96%
“…Analyses of the compressive strengths of oriented polymers have been focused on continuum mechanics treatments of anisotropic yield behavior [11], the analysis of deformation along preferential slip planes [4,7,9,11,13,15], or dislocation models for kink formation [34]. The bulk of this work indicates that failure in compression results from shear deformation or slippage between polymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…It can be argued that the tensile strength in the organic fibers is controlled by flaws and covalent bonding, while in compression fibers having a microfibrilar morphology are susceptible to fibrilation and buckling due to weak lateral van der Waals forces. Compressive failure can also occur due to weak hydrogen bonding as has been observed [4] in Kevlar. Attempts to improve compressive strength should concentrate on utilizing the stronger covalent bonding and by minimizing the weaker van der Waals forces and hydrogen bonding: entangling and crosslinking of microfibrils is a step in that direction.…”
Section: Organic Fibersmentioning
confidence: 89%
“…The factors which influence the compressive strength of fibers are discussed in this paper. directed [1][2][3][4][5][6][7][8][9] towards (i) understanding the compression behavior of these fibers, and (ii) influencing the structure and morphology of these fibers by varying processing and post-processing conditions in order to influence the compressive strength. Alterations in chemical structures [10] are also being pursued in order to achieve enhanced compressive strength.…”
Section: Introductionmentioning
confidence: 99%